2018
DOI: 10.3390/nu10040385
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and Type 2 Diabetes Mellitus in Adults: The Diabetes Mellitus Survey of Mexico City

Abstract: Diet and inflammation are both associated with type 2 diabetes mellitus (T2DM). In the present study, we aimed to assess the relation between the dietary inflammatory index (DII) and the presence of T2DM in Mexican adults participating in the Diabetes Mellitus Survey administered in Mexico City (DMS-MC). The study involved 1174 subjects (48.5% men) between 20–69 years of age. A validated semi-quantitative food frequency questionnaire was employed to evaluate dietary intake and to compute DII. The DII is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
97
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 39 publications
13
97
5
Order By: Relevance
“…Unhealthy eating habits and deleterious lifestyles, such as smoking and sedentariness, may trigger chronic inflammation thereby contributing to increased cardiometabolic risk and development of chronic noncommunicable diseases (CNCD), such as cardiovascular diseases (CVD), diabetes mellitus (DM) and cancer [1][2][3][4][5]. According to World Health Organization (WHO) in 2016, CNCD accounted for 41 million deaths, among these 17.9 million (44%) were by CVD, 9 million (22%) by cancer and 1.6 million (4%) by diabetes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Unhealthy eating habits and deleterious lifestyles, such as smoking and sedentariness, may trigger chronic inflammation thereby contributing to increased cardiometabolic risk and development of chronic noncommunicable diseases (CNCD), such as cardiovascular diseases (CVD), diabetes mellitus (DM) and cancer [1][2][3][4][5]. According to World Health Organization (WHO) in 2016, CNCD accounted for 41 million deaths, among these 17.9 million (44%) were by CVD, 9 million (22%) by cancer and 1.6 million (4%) by diabetes [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between dietary fat and bone health is controversial. 27 In regard to other dietary patterns, the results found that high intake of soft drinks, coffee, juice and fast/fried foods can adversely impact bone health. 9,28 Although, there wasn't significant values between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology and participant characteristics have been previously detailed. 14 In total, 1 174 subjects were included in the present analysis. Altogether, 242 participants were excluded for the following reasons: 142 participants had missing information regarding biomarkers and other important covariates.…”
Section: Methodsmentioning
confidence: 99%
“…Previous DM2 diagnosis methods in the DMS-CM 2015 have been previously reported. 14 In short, first subjects were asked whether or not they had a diabetic condition and whether they had ever been diagnosed with DM2 by a physician. Additionally, subjects whose glucose concentration was ≥126 mg/dL and had levels of [HbA1c (%) ≥6.5] were defined as displaying fasting glucose and/or HbA1c values consistent with DM2 diagnostic criteria 19 and were also defined as participants with DM2.…”
Section: Type 2 Diabetesmentioning
confidence: 99%